Association of Intraocular Pressure Changes With Right Ventricular Diameter and Brain Natriuretic Peptide in a Case of Pulmonary Arterial Hypertension. Issue 3 (March 2016) - Sato, Chiaki; Kaneko, Hiroki; Kondo, Takahisa; Takayama, Kei; Yasuda, Shunsuke; Terasaki, Hiroko
Abstract : Purpose: To report a case of secondary pulmonary arterial hypertension (PAH) and the relationship of intraocular pressure (IOP) change with right ventricular diameter (RVD) and brain natriuretic peptide (BNP). Methods: Case report. Patient: A 22-year-old woman with dilated and congested conjunctival and episcleral veins was diagnosed with high IOP. She was previously diagnosed with Sjögren syndrome and suffered from secondary PAH. Results: The RVD and BNP level improved and the IOP decreased with routine treatment for PAH. During self-cessation of treatment for PAH, the RVD, BNP level, and IOP deteriorated. However, they improved after treatment was reinitiated. Conclusion: There was a synchronizing change in the parameters representing high pulmonary arterial pressure and IOP during treatment of PAH.